Preparation method of aluminum oxide / titanium oxide composite ceramic powder for in-situ induction of columnar crystals

Through the preparation method of alumina/titanium oxide composite ceramic powder that induces columnar crystals in situ, the Hollandite phase induces Ba doping is solved, and the problem of difficult to take into account the sintering densification and fracture toughness of Al2O3/TiO2 ceramics is achieved efficient mechanical performance improvement and batch preparation of complex shape ceramics.

CN119219412APending Publication Date: 2024-12-31HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411416846.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing Al2O3/TiO2 composite ceramics are difficult to take into account both densification and fracture toughness during the sintering process, and the scope of TiO2 content regulation is limited, resulting in deterioration of ceramic strength and toughness.

Method used

The preparation method of alumina/titanium oxide composite ceramic powder that induces columnar crystals in situ is adopted. The aluminum powder and diluent are dried and ball milled, and then the high-temperature combustion is carried out in a high-pressure reactor. The Hollandite phase is induced by Ba doping to form sub- Micron to micron-sized columnar crystal structure, adjusting the sintering process parameters to control the growth of columnar crystals.

Benefits of technology

The sintering and densification of high-energy metastable ceramic powder is achieved, the fracture toughness and mechanical properties of the ceramic are improved, and the characteristics are high in production efficiency, low cost, and suitable for the preparation of large-size ceramics in complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219412A_ABST
    Figure CN119219412A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of in-situ induced columnar crystal aluminum oxide / titanium oxide composite ceramic powder, relates to the field of oxide composite ceramics, and aims to solve the problem of poor fracture toughness in the conventional preparation method of Al2O3 / TiO2 composite ceramics. The method comprises the following steps: 1, respectively drying aluminum powder and a diluent; the diluent is a mixture of aluminum oxide, titanium dioxide and a barium source; 2, mixing the dried aluminum powder with a diluent, performing ball milling, and sieving after ball milling to obtain mixed powder; and 3, filling the mixed powder into a high-pressure reactor, sealing, igniting the mixed powder, initiating a high-temperature combustion synthesis reaction, forming a high-temperature melt after the reaction is finished, opening a nozzle, spraying the high-temperature melt through the nozzle, spraying the high-temperature melt into an atomizing tower filled with mixed gas below, and cooling and settling to obtain the Ba-doped Al2O3 / TiO2 composite ceramic powder. The method is used for preparing the aluminum oxide / titanium oxide composite ceramic with high fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oxide composite ceramics, and in particular to a method for preparing in-situ induced columnar crystal aluminum oxide / titanium oxide composite ceramic powder. Background Art

[0002] Oxide ceramics have the characteristics of high hardness, oxidation resistance, corrosion resistance and high-temperature structural stability, and are widely used in industrial equipment, "two-machine" hot end components, protective coatings and other fields. Al2O3 ceramics are one of the most promising structural material candidates, but the high brittleness, easy fracture and poor strength determined by the intrinsic chemical bond characteristics (ionic bonds and covalent bonds) greatly limit its application and development. In addition, the melting point of Al2O3 is as high as 2072℃, and the densification of the block usually requires harsh sintering conditions: including high sintering temperature (over 1500℃) and the use of field-assisted sintering technology, which leads to high energy consumption, difficulty in process control and inevitable grain coarsening.

[0003] Adding appropriate additives is a common way to improve the sintering and performance of Al2O3 ceramics. Studies have shown that the introduction of TiO2 can significantly enhance the sintering activity and mechanical properties of ceramics in Al2O3-based ceramics. TiO2 can be partially dissolved in the alumina lattice at high temperature. Ti replaces the lattice site of Al and produces cation vacancies to balance the charge, which enhances the lattice diffusion rate of Al2O3, thereby reducing the sintering activation energy and significantly improving the density of Al2O3-based ceramics. In addition, when the amount of TiO2 added exceeds the solid solubility limit (about 0.27wt%), an additional compound phase Al2TiO5 (above 900-1280℃) will be generated at the grain boundary, which has a complex effect on the microstructure and mechanical properties of the composite ceramic. Fine and uniform Al2TiO5 grains can limit the growth of alumina grains at the grain boundary through the pinning effect, and introduce residual compressive stress in the Al2O3 grains through the thermal expansion mismatch with the matrix, inhibiting transgranular fracture to improve the strength and fracture toughness of the composite ceramic. However, when the TiO2 content is high, the production of a large amount of coarsened Al2TiO5 will weaken the toughening effect. There are significant differences in the thermal expansion coefficients of Al2TiO5 along the three main axes, which may lead to extreme stress states in local areas of the ceramic during the cooling process. Therefore, self-generated microcracks often exist in Al2O3 / TiO2 composite ceramics, and their size depends significantly on the morphology and size of Al2TiO5 grains. When the TiO2 addition amount is high or the dispersion uniformity is poor, the coarsened and penetrating microcracks formed will lead to the deterioration of the strength and toughness of the ceramic. Therefore, in the previous research on Al2O3-TiO2 system ceramics, in order to avoid excessive coarsening of Al2TiO5 grains, the adjustable range of TiO2 content is very limited.

[0004] The mechanical properties of ceramic composites can be effectively improved by introducing a one-dimensional structure (whiskers, columnar crystals, etc.) reinforcement phase into the ceramic matrix. During crack propagation, high-strength, low-defect one-dimensional materials can promote crack deflection, and further increase the energy consumption at the crack tip and promote crack closure through the pull-out or bridging mechanism, thereby improving the ability of ceramics to resist fracture. Studies have shown that the introduction of one-dimensional reinforcements such as carbon nanotubes and β-Si3N4 whiskers into Al2O3-based ceramics can effectively improve the fracture toughness of the material. However, these reinforcements are usually added to the composite system during the sintering process, and their interface compatibility with the matrix is ​​limited. Therefore, the reinforcements usually need to be pretreated to improve the surface activity and to improve the uniformity of their dispersion in the matrix through long-term mixing. In addition, high-content reinforcements are prone to agglomeration to form a rigid skeleton, which hinders the realization of block densification, which makes it difficult to control the reinforcement content and optimize the performance of the composite material. Summary of the invention

[0005] The present invention aims to solve the problem that the existing preparation method of Al2O3 / TiO2 composite ceramics cannot take into account both ceramic densification and fracture toughness, and provides a preparation method of alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals to improve the fracture toughness of Al2O3 / TiO2 ceramics.

[0006] The method for preparing the in-situ induced columnar crystal aluminum oxide / titanium oxide composite ceramic powder of the present invention comprises the following steps:

[0007] Step 1: Drying the aluminum powder and the diluent separately; the diluent is a mixture of aluminum oxide (Al2O3), titanium dioxide (TiO2) and a barium source, wherein the mass of aluminum oxide accounts for 29.6% to 92.5% of the total mass of the diluent, the mass of titanium dioxide accounts for 6.6% to 57.1% of the total mass of the diluent, and the remainder is the barium source;

[0008] Step 2: Mix the dried aluminum powder with a diluent, ball-mill, and sieve after ball-milling to obtain a mixed powder; wherein the mass percentage of the aluminum powder in the mixed powder is 14.2% to 24.5%, and the mass percentage of the diluent is 75.5% to 85.8%;

[0009] Step 3: Fill the mixed powder into the high-pressure reactor and seal it. After vacuuming, fill it with high-purity O2 or O2 mixed gas. A nozzle is provided at the bottom of the high-pressure reactor. The nozzle has a nozzle diameter of 1 to 6 mm. After maintaining the pressure for 8 to 15 minutes to confirm that the airtightness is good, ignite the mixed powder to initiate a high-temperature combustion synthesis reaction. The temperature of the reaction system is 2500 to 4000 ° C. After the reaction is completed, a high-temperature melt is formed. The temperature and pressure are maintained for 2 to 60 seconds, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle and sprayed into the atomizing tower filled with mixed gas below. After cooling and settling, Ba-doped Al2O3 / TiO2 composite ceramic powder is obtained. The pressure of the high-temperature melt ejected is 10 to 40 MPa.

[0010] Principle of the present invention:

[0011] The present invention realizes high-temperature combustion synthesis of the system and obtains a uniform oxide melt through a highly exothermic combustion reaction between aluminum powder and oxygen. After rapid cooling in a gas medium, a micron-sized ceramic powder with components uniformly mixed at the atomic scale is obtained. The powder obtained by the rapid cooling method of the high-temperature melt is in a high-energy metastable state, and there are abundant supersaturated solid solutions, amorphous phases, and a variety of metastable transition phases (high-temperature phases such as δ-Al2O3, BaAl2O4 and BaTi4O9).

[0012] The present invention uses Ba as a columnar crystal inducing agent for Al2O3-TiO2 system ceramics, and realizes Al2O3-TiO2 composite ceramics with high content and uniformly distributed columnar crystals through Ba doping. The columnar grains are formed in situ from metastable powder during the sintering process. This is because Ba doping induces a special Hollandite phase (Ba x Al y Ti 8- y O 16) formation and growth. The Ba ions in the Hollandite crystal are filled in a tunnel-like structure arranged along the c-axis (

[001] crystal direction). During the heating process, the diffusion and migration rate of the Ba ions along the c-axis is higher, and the grains grow preferentially, thereby forming a submicron to micron columnar crystal structure in the ceramic. During the sintering process, the metastable composite powder proposed by the present invention may undergo solid solution precipitation of supersaturated solid solution, transformation of metastable phase / transition phase to stable phase, and other behaviors different from the sintering of traditional equilibrium powders. Compared with traditional equilibrium powders, the metastable powder has a higher defect content and a higher diffusion rate of each component, which promotes the anisotropic growth trend of Hollandite grains. On the basis of the solid solution precipitation and amorphous crystallization of the metastable composite powder, the preferential growth behavior of the Hollandite grains can be adjusted by reasonably controlling the Ba doping amount and the sintering process parameters, thereby achieving the regulation of the grain size and aspect ratio of the columnar crystals. This in-situ construction strategy of micron-sized columnar crystals is of great significance for improving the spontaneous cracking problem caused by Al2TiO5 in Al2O3 / TiO2 composite ceramics and improving the mechanical properties of ceramics. In addition, the dendrite Al2O3 supersaturated solid solution in the metastable powder undergoes solid solution precipitation during the sintering process, forming a unique intercrystalline / intracrystalline precipitation structure, which helps to improve the fracture toughness of the ceramics.

[0013] Beneficial effects of the present invention:

[0014] 1. The Ba-doped Al2O3 / TiO2 composite powder obtained by the present invention has the characteristics of high-energy metastable state, and there are abundant defects such as vacancies and dislocations in the lattice, which is conducive to the improvement of the sintering activity of the powder. During the sintering densification process, the supersaturated solid solution undergoes precipitation and precipitation to form intercrystalline / intracrystalline precipitation structures of nanometer to submicron level. At the same time, Ba doping can induce the in-situ formation of Hollandite phase during the sintering process of Al2O3 / TiO2 ceramics. With the occurrence of solid solution precipitation, amorphous crystallization, transition phase transformation and other behaviors, the Hollandite phase can preferentially grow to form columnar grains, thereby obtaining Al2O3-based composite ceramics containing a large number of uniformly distributed columnar crystals. By adjusting the Ba doping amount and sintering process parameters, the columnar crystal content, size and aspect ratio can be regulated. The aspect ratio of the columnar crystal is as high as 5-20, and the volume fraction is 8vol% to 18vol%.

[0015] 2. The composite ceramic powder obtained by the present invention can be sintered to prepare bulk ceramics with excellent performance. The addition of TiO2 and the presence of metastable phases increase the lattice defect concentration and promote the enhancement of the lattice diffusion capacity. Through pressureless sintering, a relative density of more than 95% of bulk ceramics can be achieved at 1350-1450°C. During the fracture process, the composite ceramics exhibit a mixed mode of intergranular fracture and transgranular fracture. The high content of columnar crystals can play the role of pulling out and bridging one-dimensional grains, as well as promoting the deflection of intergranular cracks, effectively increasing the fracture resistance of the ceramics. In addition, larger-sized Al2O3 grains undergo transgranular fracture, and the fine intragranular structure formed inside them can effectively increase the path of crack propagation and further increase the energy consumption of the crack. Under the action of multiple mechanisms, the fracture toughness of Al2O3-based composite ceramics is effectively improved. Calculated as monometallic oxide, when the TiO2 content is 5-35wt% and the BaO content is 0.5-13wt%, the hardness of the composite ceramic is 10-16GPa and the fracture toughness is 4-8MPa m 1 / 2 .

[0016] 3. The method of the present invention has the characteristics of high production efficiency, low cost, and green environmental protection, and can realize the batch preparation of ceramic products with complex shapes and large sizes (existing hot pressing sintering or plasma sintering and other technologies can only prepare strip or cylindrical ceramic products). In the high-temperature melt obtained by this method, different components diffuse with each other in the liquid state, and finally achieve uniform mixing at the atomic scale in the composite powder product.

[0017] 4. The composite powder produced by the method of the present invention has a regular spherical shape and is well suited for forming technologies such as sintered blocks, spray coatings, and additive manufacturing. The rapid cooling conditions during the atomization process cause a large number of metastable phases such as supersaturated solid solutions, amorphous, and transitional compounds to form inside the powder product, which provides a basis for the preferential growth of solid solution precipitation phases and grains in subsequent sintered ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope photograph of the metastable Ba-doped Al2O3 / TiO2 ceramic powder particles prepared in Example 1;

[0019] Figure 2 The surface microstructure of the metastable Ba-doped Al2O3 / TiO2 ceramic powder prepared in Example 1;

[0020] Figure 3 The interface microstructure and element distribution analysis of the metastable Ba-doped Al2O3 / TiO2 ceramic powder prepared in Example 1;

[0021] Figure 4 The microstructure and element distribution analysis of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 1;

[0022] Figure 5 The crack deflection behavior of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 1 during the crack propagation process;

[0023] Figure 6 The columnar crystal bridging / pull-out toughening behavior during crack propagation of the columnar crystal Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 1;

[0024] Figure 7 TEM photo of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 2;

[0025] Figure 8 A lattice fringe photograph and a schematic diagram of the oriented growth direction of a HRTEM photograph of a columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 2;

[0026] Fig. 9 The FFT calibration result of the lattice fringes of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 2;

[0027] Fig.10 This is a STEM-HAADF photograph of the intracrystalline precipitation structure of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 3;

[0028] Fig.11 This is a BSE photograph of the columnar Ba-doped Al2O3 / TiO2 composite ceramic prepared in Example 4. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0030] Specific implementation method 1: The preparation method of the in-situ induced columnar alumina / titanium oxide composite ceramic powder of this implementation method specifically includes the following steps:

[0031] Step 1: Drying the aluminum powder and the diluent separately; the diluent is a mixture of aluminum oxide (Al2O3), titanium dioxide (TiO2) and a barium source, wherein the mass of aluminum oxide accounts for 29.6% to 92.5% of the total mass of the diluent, the mass of titanium dioxide accounts for 6.6% to 57.1% of the total mass of the diluent, and the remainder is the barium source;

[0032] Step 2: Mix the dried aluminum powder with a diluent, ball-mill, and sieve after ball-milling to obtain a mixed powder; wherein the mass percentage of the aluminum powder in the mixed powder is 14.2% to 24.5%, and the mass percentage of the diluent is 75.5% to 85.8%;

[0033] Step three: Load the mixed powder into a high-pressure reactor and seal it. After vacuuming, fill it with high-purity O2 or O2 mixed gas. A nozzle is provided at the bottom of the high-pressure reactor. The nozzle has a nozzle diameter of 1 to 6 mm. After maintaining the pressure for 8 to 15 minutes to confirm that the airtightness is good, ignite the mixed powder to initiate a high-temperature combustion synthesis reaction. The temperature of the reaction system is 2500 to 4000°C. After the reaction is completed, a high-temperature melt is formed. The heat and pressure are maintained for 2 to 60 seconds, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle and sprayed into the atomizing tower filled with mixed gas below. After cooling and settling, Ba-doped Al2O3 / TiO2 composite ceramic powder is obtained.

[0034] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the aluminum powder in step 1 is dried in vacuum, inert gas or reducing gas. The rest is the same as specific implementation method 1.

[0035] The vacuum degree of the vacuum drying in this embodiment is 0.05 to 0.09 MPa.

[0036] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the drying temperature in step 1 is 60-100° C. and the drying time is 8-14 hours. The rest is the same as specific implementation method 1 or 2.

[0037] Specific embodiment 4: This embodiment differs from any one of specific embodiments 1 to 3 in that the barium source in step 1 is barium carbonate (BaCO3), barium oxide (BaO) or barium nitrate (Ba(NO3)2). The rest is the same as any one of specific embodiments 1 to 3.

[0038] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the ball-to-material mass ratio in step 2 is 3:1, and the ball-milling time is 2 to 12 hours. The rest is the same as specific embodiments 1 to 4.

[0039] Specific implementation method 6: This implementation method is different from the specific implementation methods 1 to 5 in that: in step 2, the ball milling is followed by passing through a 40-200 mesh sieve. The rest is the same as the specific implementation methods 1 to 5.

[0040] Specific implementation example 7: This implementation example is different from specific implementation examples 1 to 6 in that the O2 mixed gas in step 3 is a mixed gas of oxygen and an inert gas. The rest is the same as specific implementation examples 1 to 6.

[0041] The inert gas in this embodiment is argon (Ar), which has the lowest cost.

[0042] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the mixed gas filled in the atomizing tower in step 3 is air, a mixed gas of O2 and N2, or a mixed gas of N2 and an inert gas. The rest is the same as specific embodiments 1 to 7.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the obtained Ba-doped Al2O3 / TiO2 composite ceramic powder is sintered to obtain an alumina / titanium dioxide composite ceramic containing in-situ self-generated columnar crystals. The rest is the same as specific embodiments 1 to 8.

[0044] The present invention obtains a high-temperature melt by ultra-high temperature combustion synthesis between aluminum powder and oxygen. After the melt is rapidly cooled by a gas medium, a ceramic powder containing a mixture of metastable phases (amorphous, supersaturated solid solution and transitional high-temperature phase) is obtained. This powder has the characteristics of high-energy metastable state. During sintering and densification, the metastable phase transforms into a stable product, and the powder undergoes behaviors such as amorphous crystallization and precipitation precipitation to form a fine intercrystalline / grain boundary composite structure. And as solid-state diffusion proceeds, the transition phase transforms, prompting the in-situ formation of the Hollandite phase. The Ba ions in the Hollandite crystal are filled in a tunnel-like structure arranged along the c-axis (

[001] crystal direction). During the heating process, the Ba ions are more likely to diffuse and migrate along the c-axis, triggering the preferential growth of grains, thereby forming a submicron to micron-level columnar crystal structure in the ceramic. The generation of this type of structure can greatly increase the crack propagation path, promote the energy consumption at the crack tip, and thus effectively improve the mechanical properties of the ceramic. This type of structure is difficult to achieve in ceramics sintered by equilibrium powder in the past.

[0045] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that the sintering process is pressureless sintering, hot pressing sintering and spark plasma sintering. The rest is the same as specific embodiment 9.

[0046] The pressureless sintering process described in this embodiment is conventional pressureless sintering, vacuum sintering or atmosphere sintering.

[0047] Specific embodiment 11: This embodiment differs from specific embodiment 9 or 10 in that the sintering process conditions are: sintering temperature 1300-1550°C, heating rate 4-200°C / min, and holding time 5min-6h. Others are the same as specific embodiment 9 or 10.

[0048] Specific embodiment 12: This embodiment differs from specific embodiment 9 or 10 in that the sintering process conditions are: firstly medium-low temperature sintering at 800-1200°C, then high temperature sintering at 1300-1550°C, heating rate 5-200°C / min, holding time 5min-6h. Others are the same as specific embodiment 9 or 10.

[0049] Composite micron powders containing a large amount of metastable phases can be initially sintered at medium to low temperatures to cause metastable phase transformation and induce the formation and growth of columnar crystals, and then densified through high-temperature rapid sintering.

[0050] Specific embodiment 13: This embodiment differs from specific embodiment 1 in that the obtained Ba-doped Al2O3 / TiO2 composite ceramic powder is subjected to high-energy ball milling to 100-500nm and then pressureless sintering. The rest is the same as specific embodiment 1.

[0051] In this embodiment, the prepared metastable barium-doped alumina / titanium oxide composite ceramic powder is ball-milled into a submicron powder, which can reduce the sintering temperature and inhibit the growth of grains. In addition, this method can break up metastable grains and structures, accelerate the reaction and phase change during the sintering process, refine the size of columnar crystals and increase their formation rate.

[0052] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation schemes and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0053] Embodiment 1:

[0054] The preparation method of the in-situ induced columnar crystal 2wt%BaO doped Al2O3 / 13wt%TiO2 composite ceramic in this embodiment is specifically completed by the following steps:

[0055] 1. Drying aluminum powder, aluminum oxide powder, titanium dioxide powder and barium carbonate powder, wherein the aluminum powder is dried under a vacuum degree of 0.05 MPa, a drying temperature of 80°C, and a drying time of 8 hours; the aluminum oxide powder, titanium dioxide powder and barium carbonate powder are dried under normal pressure, a drying temperature of 80°C, and a drying time of 8 hours;

[0056] 2. Mix 189g aluminum powder, 633g aluminum oxide powder, 148g titanium dioxide powder and 30g barium carbonate powder after drying, and place them in a planetary ball mill for ball milling, with a ball-to-material mass ratio of 3:1 and a ball milling time of 6h. After ball milling, pass through a 60-mesh sieve to obtain a mixed material;

[0057] 3. Load the mixed material into a high-pressure reactor and fill it with high-purity O2. The oxygen pressure is set to 20MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle opening size is Ф2.5mm. Place the high-pressure reactor above the gas cooling device. Power is passed through the resistance wire to ignite the mixed material to carry out a high-temperature combustion synthesis reaction. The theoretical reaction temperature is 3300°C. After the reaction is completed, a high-temperature melt is formed. After keeping the temperature for 8s, the nozzle is opened. Under high temperature and high pressure environment, the high-temperature melt is ejected through the nozzle. The melt ejection pressure is 25MPa and is sprayed into the air cooling device for gas phase cooling. After the particles are settled, barium-doped alumina / titanium dioxide composite ceramic powder is obtained. The air cooling device is an atomizing tower filled with a cooling gas medium, and the cooling gas is air.

[0058] Fourth, the powder obtained in step 3 was ball-milled at a speed of 200 r / min to obtain a powder with an average particle size of 500 nanometers, and then pressed into a green body under uniaxial pressure. The green body was subjected to pressureless sintering to obtain columnar crystal 2wt%BaO doped Al2O3 / 13wt%TiO2 ceramics, and the pressureless sintering conditions were: sintering temperature 1350°C, heat preservation 6h, and heating rate 5°C / min.

[0059] The ceramic prepared in this example was subjected to Vickers indentation test and three-point bending test, and its performance was: hardness 14.42 GPa, fracture toughness 5.47 MPa·m 1 / 2 .

[0060] The Al2O3 / 13wt%TiO2 / 2wt%BaO composite powder prepared in Example 1 was characterized by its microstructure. Figure 1 and Figure 2 shown. Figure 1 This is a scanning electron microscope photo of the composite ceramic powder particles obtained in step 3 of Example 1. It can be seen that the powder has a regular spherical shape and a typical dendrite structure (such as Figure 2 ). Figure 3 The BSE photo of the cross section of the composite ceramic powder (the photo in the upper left corner) and the electron probe-wavelength dispersion spectrum analysis results show that the internal structure of the atomized quenched powder is composed of dendrites and fine intergranular structure, and the elemental composition is evenly distributed. The dendrites are supersaturated solid solutions of Al2O3 that have dissolved a large amount of Ti and Ba elements. Figure 4 The scanned image of Al2O3 / 13wt%TiO2 / 2wt%BaO ceramic after pressureless sintering is shown. The overall structure is uniform and dense, and high-density submicron / micron-sized columnar crystals are formed in situ in the ceramic. Due to the pinning effect of the columnar crystals at the grain boundary and the competitive growth with the Al2TiO5 grains, the growth of Al2TiO5 is inhibited, and no obvious spontaneous cracks are generated inside the ceramic. The columnar crystals formed in situ are evenly distributed at the grain boundaries of the equiaxed grains of the matrix, and the aspect ratio reaches 5-15.

[0061] Figure 5 and Figure 6 It is a BSE photograph of the crack propagation path of the Vickers indentation of the composite ceramic. The ceramic exhibits a mixed mode of transgranular fracture and intergranular fracture. When the intergranular crack extends to the columnar crystal, the columnar crystal causes the crack to deflect to extend the propagation path. At the same time, the pull-out and bridging behavior of the columnar crystal are observed. These mechanisms effectively improve the fracture toughness of the ceramic.

[0062] Embodiment 2:

[0063] The preparation method of the in-situ induced columnar crystal 1wt%BaO doped Al2O3 / 5wt%TiO2 composite ceramic in this embodiment is specifically completed by the following steps:

[0064] 1. Drying aluminum powder, aluminum oxide powder, titanium dioxide powder and barium carbonate powder, wherein the aluminum powder is dried under a vacuum degree of 0.05 MPa, a drying temperature of 80°C, and a drying time of 8 hours; the aluminum oxide powder, titanium dioxide and barium carbonate powder are dried under normal pressure, a drying temperature of 100°C, and a drying time of 8 hours;

[0065] 2. Mix 216g aluminum powder, 710g aluminum oxide powder, 59g titanium dioxide powder and 15g barium carbonate powder after drying, and place them in a planetary ball mill for ball milling, with a ball-to-material mass ratio of 3:1 and a ball milling time of 8h. After ball milling, pass through a 60-mesh sieve to obtain a mixed material;

[0066] 3. Load the mixed material into a high-pressure reactor and fill it with high-purity O2. The oxygen pressure is set to 23MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle opening size is Ф3mm. Place the high-pressure reactor above the gas cooling device. Power is passed through the resistance wire to ignite the mixed material to carry out a high-temperature combustion synthesis reaction. The theoretical reaction temperature is 3500°C. After the reaction is completed, a high-temperature melt is formed. After keeping the temperature for 10 seconds, the nozzle is opened. Under high temperature and high pressure environment, the high-temperature melt is ejected through the nozzle. The melt ejection pressure is 28MPa and is sprayed into the air cooling device for gas phase cooling. After the particles are settled, barium-doped alumina / titanium dioxide composite ceramic powder is obtained. The air cooling device is an atomizing tower filled with a cooling gas medium, and the cooling gas is air.

[0067] Fourth, the powder obtained in step 3 was ball-milled at a speed of 200 r / min to obtain a powder with an average particle size of 300 nanometers, and then pressed into a green body under uniaxial pressure. The green body was subjected to pressureless sintering to obtain columnar crystal 1wt%BaO doped Al2O3 / 5wt%TiO2 ceramics, and the pressureless sintering conditions were: sintering temperature 1400°C, heat preservation 6h, and heating rate 5°C / min.

[0068] The ceramic prepared in this example was subjected to Vickers indentation test and three-point bending test, and its performance was: hardness 15.22 GPa, fracture toughness 4.47 MPa·m 1 / 2 .

[0069] The TEM image of the Al2O3 / 5wt%TiO2 / 1wt%BaO composite ceramic obtained in Example 2 shows columnar grains distributed in the matrix, such as Figure 7 As shown. Figure 8 and Fig. 9 As shown in the figure, the lattice fringe calibration results of the HRTEM image show that the columnar crystals generated in situ are Hollandite phases that grow preferentially along the c-axis. The columnar crystals with an aspect ratio of 8-15 are evenly distributed in the matrix composed of equiaxed grains, which effectively improves the crack propagation resistance and thus enhances the mechanical properties of the ceramic.

[0070] Embodiment 3:

[0071] The preparation method of the in-situ induced columnar crystal 3wt%BaO doped Al2O3 / 20wt%TiO2 composite ceramic in this embodiment is specifically completed by the following steps:

[0072] 1. Drying aluminum powder, aluminum oxide powder, titanium dioxide powder and barium carbonate powder, wherein the aluminum powder is dried under a vacuum degree of 0.05 MPa, a drying temperature of 80°C, and a drying time of 8 hours; the aluminum oxide powder, titanium dioxide and barium carbonate powder are dried under normal pressure, a drying temperature of 100°C, and a drying time of 8 hours;

[0073] 2. Mix 185g aluminum powder, 543g aluminum oxide powder, 228g titanium dioxide powder and 44g barium carbonate powder after drying, and place them in a planetary ball mill for ball milling, with a ball-to-material mass ratio of 3:1, and the ball milling time is 6h. After ball milling, pass through a 60-mesh sieve to obtain a mixed material;

[0074] 3. Load the mixed material into a high-pressure reactor and fill it with high-purity O2. The oxygen pressure is set to 19MPa. A nozzle is provided at the lower end of the high-pressure reactor with a nozzle opening size of Ф2.5mm. Place the high-pressure reactor above a gas cooling device. Power is passed through the resistance wire to ignite the mixed material to carry out a high-temperature combustion synthesis reaction. The theoretical reaction temperature is 3200°C. After the reaction is completed, a high-temperature melt is formed. After keeping the temperature for 8s, the nozzle is opened. Under high temperature and high pressure environment, the high-temperature melt is ejected through the nozzle with a melt ejection pressure of 24MPa. It is sprayed into an air cooling device for gas phase cooling. After the particles are settled, barium-doped alumina / titanium dioxide composite ceramic powder is obtained; the air cooling device is an atomizing tower filled with a cooling gas medium, and the cooling gas is air;

[0075] Fourth, the powder obtained in step 3 was ball-milled at a speed of 200 r / min to obtain a powder with an average particle size of 500 nanometers, and then pressed into a green body under uniaxial pressure. The green body was subjected to pressureless sintering to obtain columnar crystal 3wt%BaO doped Al2O3 / 20wt%TiO2 ceramics, and the pressureless sintering conditions were: sintering temperature 1350°C, heat preservation 6h, and heating rate 5°C / min.

[0076] The ceramic prepared in this example was subjected to Vickers indentation test and three-point bending test, and its performance was: hardness 13.37 GPa, fracture toughness 5.18 MPa·m 1 / 2 .

[0077] The Al2O3 / 20wt%TiO2 / 3wt%BaO composite ceramic block prepared in Example 3 has a high content of columnar crystals. In addition, the supersaturated solid solution undergoes precipitation during sintering, forming a nano- to submicron-sized intracrystalline / intercrystalline precipitation structure. The STEM-HAADF image of the ceramic shows that there are fine granular precipitation phases inside the large-sized Al2O3 grains, such as Fig.10 As shown in Figure 2, during the fracture process of ceramics, the columnar crystal structure and the precipitated particles within the crystal can effectively promote the improvement of the fracture toughness of ceramics.

[0078] Embodiment 4:

[0079] The preparation method of the in-situ induced columnar crystal 6wt%BaO doped Al2O3 / 40wt%TiO2 composite ceramic in this embodiment is specifically completed by the following steps:

[0080] 1. Drying aluminum powder, aluminum oxide powder, titanium dioxide powder and barium carbonate powder, wherein the aluminum powder is dried under a vacuum degree of 0.05 MPa, a drying temperature of 80°C, and a drying time of 8 hours; the aluminum oxide powder, titanium dioxide powder and barium carbonate powder are dried under normal pressure, a drying temperature of 80°C, and a drying time of 8 hours;

[0081] 2. Mix 165g aluminum powder, 325g aluminum oxide powder, 424g titanium dioxide powder and 86g barium carbonate powder after drying, and place them in a planetary ball mill for ball milling, with a ball-to-material mass ratio of 3:1 and a ball milling time of 6h. After ball milling, pass through a 60-mesh sieve to obtain a mixed material;

[0082] 3. Load the mixed material into a high-pressure reactor and fill it with high-purity O2. The oxygen pressure is set to 18MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle opening size is Ф3mm. Place the high-pressure reactor above the gas cooling device. Power is passed through the resistance wire to ignite the mixed material to carry out a high-temperature combustion synthesis reaction. The theoretical reaction temperature is 3000°C. After the reaction is completed, a high-temperature melt is formed. After keeping the temperature for 8s, the nozzle is opened. Under high temperature and high pressure environment, the high-temperature melt is ejected through the nozzle. The melt ejection pressure is 23MPa and is sprayed into the air cooling device for gas phase cooling. After the particles are settled, the composite ceramic powder is obtained. The air cooling device is an atomizing tower filled with a cooling gas medium, and the cooling gas is air.

[0083] Fourth, the powder obtained in step 3 was ball-milled to an average particle size of 500 nanometers, and then pressed into a green body under uniaxial pressure. The green body was subjected to pressureless sintering to obtain columnar crystal 6wt%BaO doped Al2O3 / 40wt%TiO2 ceramics, and the pressureless sintering conditions were: sintering temperature 1350°C, heat preservation 6h, and heating rate 5°C / min.

[0084] The ceramic prepared in this example was subjected to Vickers indentation test and three-point bending test, and its properties were: hardness 11.72 GPa, fracture toughness 4.92 MPa·m 1 / 2 .

[0085] The Al2O3 / 40wt%TiO2 / 6wt%BaO composite ceramic block prepared in Example 4 was characterized by BSE. Fig.11 As shown. High-content Hollandite columnar crystals are uniformly distributed in the ceramic matrix composed of Al2O3 and Al2TiO5 grains. The presence of such columnar crystals can play the pull-out and bridging mechanism of one-dimensional grains and promote crack deflection, thereby enhancing the mechanical properties of the ceramic. Compared with the composite ceramic Al2O3 / 13wt%TiO2 / 2wt%BaO with lower TiO2 and BaO doping amounts, the columnar crystal size is relatively coarsened, and the aspect ratio is reduced by 6 to 12. Therefore, the growth morphology of the in-situ generated columnar crystals can be regulated by reasonable control of the doping amount.

[0086] Embodiment 5:

[0087] The preparation method of the in-situ induced columnar crystal 3wt%BaO doped Al2O3 / 13wt%TiO2 composite ceramic in this embodiment is specifically completed by the following steps:

[0088] 1. Drying aluminum powder, aluminum oxide powder, titanium dioxide powder and barium oxide powder, wherein the aluminum powder is dried under a vacuum degree of 0.05 MPa, a drying temperature of 80°C, and a drying time of 8 hours; the aluminum oxide powder, titanium dioxide powder and barium oxide powder are dried under normal pressure, a drying temperature of 80°C, and a drying time of 8 hours;

[0089] 2. Mix 207g aluminum powder, 609g aluminum oxide powder, 149g titanium dioxide powder and 35g barium carbonate powder after drying, and place them in a planetary ball mill for ball milling, with a ball-to-material mass ratio of 3:1 and a ball milling time of 6h. After ball milling, pass through a 60-mesh sieve to obtain a mixed material;

[0090] 3. Load the mixed material into a high-pressure reactor and fill it with high-purity O2. The oxygen pressure is set to 22MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle opening size is Ф3mm. Place the high-pressure reactor above the gas cooling device. Power is passed through the resistance wire to ignite the mixed material to carry out a high-temperature combustion synthesis reaction. The theoretical reaction temperature is 3500°C. After the reaction is completed, a high-temperature melt is formed. After keeping the temperature for 8s, the nozzle is opened. Under high temperature and high pressure environment, the high-temperature melt is ejected through the nozzle. The melt ejection pressure is 24MPa and is sprayed into the air cooling device for gas phase cooling. After the particles are settled, the composite ceramic powder is obtained. The air cooling device is an atomizing tower filled with a cooling gas medium, and the cooling gas is air.

[0091] Fourth, the powder obtained in step 3 was ball-milled to a powder with an average particle size of 500 nanometers, and then pressed into a green body under uniaxial pressure. The green body was subjected to spark plasma sintering to obtain columnar crystal 3wt%BaO doped Al2O3 / 13wt%TiO2 ceramics, and the pressureless sintering conditions were: sintering temperature 1300°C, pressure 40MPa, heat preservation 10min, and heating rate 100°C / min.

[0092] The ceramic prepared in this example was subjected to Vickers indentation test and three-point bending test, and its properties were: hardness 16.21 GPa, fracture toughness 6.53 MPa·m 1 / 2 .

Claims

1. A method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals, characterized in that: The method comprises the following steps: Step 1: Drying the aluminum powder and the diluent separately; the diluent is a mixture of aluminum oxide, titanium dioxide and a barium source, wherein the mass of aluminum oxide accounts for 29.6% to 92.5% of the total mass of the diluent, the mass of titanium dioxide accounts for 6.6% to 57.1% of the total mass of the diluent, and the remainder is the barium source; Step 2: Mix the dried aluminum powder with a diluent, ball-mill, and sieve after ball-milling to obtain a mixed powder; wherein the mass percentage of the aluminum powder in the mixed powder is 14.2% to 24.5%, and the mass percentage of the diluent is 75.5% to 85.8%; Step three: Load the mixed powder into a high-pressure reactor and seal it. After vacuuming, fill it with high-purity O2 or O2 mixed gas. A nozzle is provided at the bottom of the high-pressure reactor. The nozzle has a nozzle diameter of 1 to 6 mm. After maintaining the pressure for 8 to 15 minutes to confirm that the airtightness is good, ignite the mixed powder to initiate a high-temperature combustion synthesis reaction. The temperature of the reaction system is 2500 to 4000°C. After the reaction is completed, a high-temperature melt is formed. The temperature and pressure are maintained for 2 to 60 seconds, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle and sprayed into the atomizing tower filled with mixed gas below. After cooling and settling, Ba-doped Al2O3 / TiO2 composite ceramic powder is obtained; wherein the pressure of the high-temperature melt ejected is 10 to 40MPa.

2. The method for preparing an in-situ induced columnar alumina / titanium oxide composite ceramic powder according to claim 1, characterized in that: The barium source in step 1 is barium carbonate, barium oxide or barium nitrate.

3. The method for preparing an in-situ induced columnar alumina / titanium oxide composite ceramic powder according to claim 1 or 2, characterized in that: After ball milling in step 2, the product is sieved through a 40-200 mesh sieve.

4. The method for preparing an in-situ induced columnar alumina / titanium oxide composite ceramic powder according to claim 1, characterized in that: The O2 mixed gas in step 3 is a mixed gas of oxygen and inert gas.

5. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 1, characterized in that: The mixed gas filled in the atomizing tower in step 3 is air, a mixed gas of O2 and N2, or a mixed gas of N2 and an inert gas.

6. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 1, characterized in that: The obtained Ba-doped Al2O3 / TiO2 composite ceramic powder is sintered to obtain an alumina / titanium dioxide composite ceramic containing in-situ self-generated columnar crystals.

7. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 6, characterized in that: The sintering process includes pressureless sintering, hot pressing sintering and spark plasma sintering.

8. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 6 or 7, characterized in that: The sintering process conditions are: sintering temperature 1300-1550° C., heating rate 4-200° C. / min, and holding time 5 min-6 h.

9. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 6 or 7, characterized in that: The sintering process conditions are: firstly medium-low temperature sintering at 800-1200° C., then high temperature sintering at 1300-1550° C., the heating rate is 5-200° C. / min, and the heat preservation time is 5min-6h.

10. The method for preparing an alumina / titanium oxide composite ceramic powder with in-situ induced columnar crystals according to claim 7, characterized in that: Before the pressureless sintering, the obtained Ba-doped Al2O3 / TiO2 composite ceramic powder is firstly subjected to high-energy ball milling to 100-500nm, and then pressureless sintering is performed.

Citation Information

Patent Citations

  • Method for preparing mixture of alumina based amorphous and solid solution ceramic micron powder by high temperature melt quenching method

    CN108821782A

  • Preparation method of columnar crystal alumina / zirconia composite ceramic powder

    CN113511884A